Chemical deterioration and physical instability of food powders - Intipunya P. (2015)
Physical and chemical deteriorations of food powders affect functionality of the powders during handling and utilization. Understanding of physical and chemical changes of food powders during storage can lead to better quality control and management to achieve powders with their intended functions. The principles of powder structure, basic and functional properties, techniques for formation of powders and manipulation of their properties are explained in this chapter. Physical changes, including stickiness, caking, structural collapse, crystallization, and loss of flowability and protein solubility, are the major causes of physical quality degradation of food powders. Maillard browning, release of free fats, and loss of volatiles in encapsulated powders are examples of chemical deteriorations during storage. Phenomena related to glass transition, and its effect on powder stability, are highlighted. Several approaches for prevention of physical instability and chemical deterioration are also suggested. © 2010 Woodhead Publishing Limited All rights reserved.